Compositional modification of products from Co-Pyrolysis of chicken manure and biomass by shifting carbon distribution from pyrolytic oil to syngas using CO2. (15th June 2018) - Choi, Dongho; Oh, Jeong-Ik; Baek, Kitae; Lee, Jechan; Kwon, Eilhann E.
Abstract: Co-pyrolysis of chicken manure and biomass was investigated in this study. The pyrolysis of individual samples was characterized by thermogravimetric analysis (TGA) under N2 and CO2 atmospheres. This demonstrated that the impact of CO2 content on the physical aspects of pyrolysis such as onset and end temperatures, and residual mass was negligible. However, a high CaCO3 content (17 wt%) in chicken manure catalyzed the Boudouard reaction. Despite its negligible physical influence, CO2 evidently affected the co-pyrolysis of chicken manure and biomass chemically. It expedited the thermal cracking of hydrocarbons from the co-pyrolysis of chicken manure and biomass. Moreover, between 550 and 660 °C, CO2 reacted with condensable hydrocarbons, effectively improving CO generation. This observation suggested that CO2 acted as both carbon scavenger and oxygen donor in the co-pyrolysis of chicken manure and biomass, a driving force for shifting carbon distribution between pyrogenic products. For example, pyrolytic oil was transformed into syngas, especially CO, offering an innovative means to modify compositions of pyrolytic products. These effects were not observed in the presence of CaCO3 and/or CaO. Highlights: The high content of CaCO3 in chicken manure catalytically enhances the Boudouard reaction. Establishing waste-to-energy via co-pyrolysis of chicken manure and lignocellulosic biomass. The enhanced thermal cracking of tar using CO2 . CO2 acted like a donor of C and O to form CO, which results in the more generation of syngas.